Biomass allocation in response to salinity and competition in native and invasive species. Issue 1 (26th January 2022) - Tang, Long; Zhou, Qing Shi; Gao, Yang; Li, Peng
Abstract: Biomass allocation to different plant parts affects the subsequent capture rate of resources and reproduction. Thus, many studies have been conducted on the biomass allocation to learn growth, reproduction, and competitive ability of plants. However, few researchers have explored how biomass allocation responses to nonresource factor and interspecific competition over time. We experimentally investigated the effects of soil salinity and competition on root : shoot ratio (RS), reproductive effort (RE; seed biomass : total biomass ratio), the relationship between belowground and aboveground biomass, the relationship between reproductive and vegetative biomass, growth, and reproduction of invasive Spartina alterniflora and native Phragmites australis . The biomass of P. australis decreased with increasing salinity, whereas that of S. alterniflora did not significantly change. The reproduction of P. australis decreased with increasing salinity under competitive conditions, and that of S. alterniflora increased. Therefore, P. australis was less‐tolerant, and S. alterniflora was more‐tolerant. The RS of P. australis increased over time under competitive conditions and with increasing salinity, and that of S. alterniflora did not significantly change. The RE of P. australis decreased to zero with decreasing total biomass, and that of S. alterniflora did not significantly correlate with total biomass. Both species exhibited a linear relationship between belowground and aboveground biomass. The relationship between reproductive and vegetative biomass in P. australis was linear, and the reproductive biomass of S. alterniflora did not significantly correlate with the vegetative biomass. Competitive dominance shifted from P. australis to S. alterniflora with increasing salinity. The findings demonstrated that the plastic biomass allocation of less‐tolerant species facilitates performance of less‐tolerant species in favorable environments, while the fixed biomass allocation of more‐tolerant species facilitates performance of more‐tolerant species in stressful environments, suggesting that S . alterniflora invasion driven by competitive exclusion probably occur in high salinity zones, and reproductive ability of invasive species should be relatively stronger during exclusion. More broadly, linking level of environmental stresses with tolerance of plants is crucial to understanding and predicting the biomass allocation and its effects on plant performance, which is an expansion of predictions from optimal theory and allometric theory and therefore illustrates the conditionality of these predictions.